The battle of the bard : Shakespeare on U.S. radio in 1937 - Jensen, Michael P. (Recreational Shakespeare., 2018)
Difficult as it is to imagine today, in 1937 America's two leading media companies fought over the right to perform Shakespeare for an American radio audience in an attempt to bring prestige to their networks. The resulting fourteen broadcasts are among the more remarkable recreations of Shakespeare of their time. This lively and engaging book shows the cultural dominance of radio in the 1930s, and tells the story of why the networks each wanted to lord Shakespeare's prestige over the other, how they put their series together, the critical reception, and the cultural impact and legacies of the broadcasts.